Lipooligosaccharides from Treponema hyodysenteriae and Treponema innocens. - Halter, M R (1988)
Lipooligosaccharides from Treponema hyodysenteriae serotypes 1 through 7, attenuated T. hyodysenteriae serotypes 1 and 2, and five strains of T. innocens were extracted with hot phenol water. The extracts were subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis separation and analyzed by lipopolysaccharide selective silver staining and Western blot (immunoblot) immunodetection. Silver staining revealed the presence of two bands that ranged between 18,000 and 24,000 daltons and that were serotype specific for T. hyodysenteriae. Attenuation of pathogenic strains resulted in the loss of the higher-molecular-weight band. Four of five T. innocens strains also lacked this particular band. T. innocens 421 had six bands between 17,000 and 26,900 daltons. Western blots with hyperimmune rabbit sera and convalescent-phase swine sera revealed antigenic variation among serotypes of T. hyodysenteriae and attenuated serotypes of T. hyodysenteriae. Convalescent-phase swine sera failed to recognize lipopolysaccharides from T. innocens. Differences in results obtained by lipopolysaccharide selective silver staining versus immunoblotting of the lipopolysaccharide preparations probably indicate that these two methods identify separate characteristics of the same molecule.